2011
DOI: 10.1111/j.1365-2117.2011.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and evolution of mass transport deposits in the South Caspian Basin, Azerbaijan

Abstract: The Quaternary to late Pliocene sedimentary succession along the margin of the South Caspian Basin contains numerous kilometre-scale submarine slope failures, which were sourced along the basin slope and from the inclined £anks of contemporaneous anticlines.This study uses three-dimensional (3D) seismic re£ection data to visualise the internal structure of 27 mass transport deposits and catalogues the syndepositional structures contained within them.These are used to interpret emplacement processes occurring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Boundary conditions at the ends of the shear band prescribe zero displacements 16) where the first condition is satisfied by equation (3.16) automatically, while the second one can be approximated as 17) leading to the following relationship (figure 6):…”
Section: Z = F(x)mentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary conditions at the ends of the shear band prescribe zero displacements 16) where the first condition is satisfied by equation (3.16) automatically, while the second one can be approximated as 17) leading to the following relationship (figure 6):…”
Section: Z = F(x)mentioning
confidence: 99%
“…According to the geological data, this landslide generated a tsunami wave with a height of 10-12 m on the coast of Norway; on the Shetland Islands, it was higher than 20 m [13]. Many other examples exist in the geological record and are often observed on industry-acquired geophysical data [14][15][16]. The common features of the above landslides are that they are very long (10 1 -10 2 km), relatively shallow (less than 10 2 m thick) and occur in very mild continental slopes (inclination less than 10 −1 ) built of normally consolidated sediments.…”
Section: Introduction (A) Submarine Landslidesmentioning
confidence: 99%
“…These correspond to the initial definition of mass-transport deposits (MTDs) proposed by Weimer (1989). Reviews of MTDs imaged by better quality seismics than in that initial work can be found in Moscardelli et al (2006) and Bull et al (2009); a detailed study of MTDs around the Shah Deniz anticline is provided by Richardson et al (2011). In the present article, the four MTDs are numbered MTD 1 to MTD 4 from the top of the section downward.…”
Section: Regional Stratigraphymentioning
confidence: 68%
“…In this prolific onshore and offshore oil and gas province, sediment remobilization has been the subject of numerous publications this last decade, in particular related to mud volcanoes (e.g., Fowler et al 2000;Planke et al 2003;Yusifov and Rabinowitz 2004;Evans et al 2006) and mud volcano systems . More recently, Richardson et al (2011) focused on mass-transport complexes. The present study investigates a massive (several kilometers in diameter), buried crater-like structure associated with a mass-transport deposit at the crest of the Absheron anticline.…”
Section: Introductionmentioning
confidence: 99%
“…Gee et al, 2006;Loncke et al, 2009;Richardson et al, 2011). Typically, limiting equilibrium (LE) analysis underlies the probabilistic modelling, which assumes that failure takes place simultaneously along the entire sliding surface where the shear stress exceeds the peak shear strength.…”
Section: Introductionmentioning
confidence: 99%